2014
DOI: 10.1186/1471-2334-14-411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deworming on school-aged children’s physical fitness, cognition and clinical parameters in a malaria-helminth co-endemic area of Côte d’Ivoire

Abstract: BackgroundMalaria and helminth infections are thought to negatively affect children’s nutritional status and to impair their physical and cognitive development. Yet, the current evidence-base is weak. The purpose of this study was to determine the effect of deworming against soil-transmitted helminthiasis and schistosomiasis on children’s physical fitness, cognition and clinical parameters in a malaria-helminth co-endemic setting of Côte d’Ivoire.MethodsWe designed an intervention study with a 5-month follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 64 publications
4
36
0
Order By: Relevance
“…Unexpectedly, the VO 2 max was slightly lower after treatment although this difference was not significant. In line with the study of Bustinduy and colleagues [11], the study found a significant association between fitness and nutritional deficiencies [14]. …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Unexpectedly, the VO 2 max was slightly lower after treatment although this difference was not significant. In line with the study of Bustinduy and colleagues [11], the study found a significant association between fitness and nutritional deficiencies [14]. …”
Section: Discussionsupporting
confidence: 81%
“…Hürlimann and colleagues [14] investigated 219 children aged 8–14 years before and after deworming. Only one stool, urine and blood sample was collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three common STH species that infect the school children are roundworm ( Ascaris lumbricoides ), whipworm ( Trichuris trichiura ), and hookworms. Often, two or more STH species are harbored by a child; and the infections are associated with poor growth, reduced physical activity, and impaired cognitive function and learning ability [3]. …”
Section: Introductionmentioning
confidence: 99%
“…34 Studies in other countries suggest that the impact of deworming in endemic areas is likely undermined by other widespread infectious diseases and nutritional deficiencies. 35 This needs to be studied in Honduras.…”
Section: Notementioning
confidence: 99%